PERAN NEGARA HUKUM INDONESIA MELINDUNGI RAKYATNYA DALAM MENYAMBUT MASYARAKAT EKONOMI ASEAN (MEA) 2015 - Yuswanto, Yuswanto (FIAT JUSTISIA, 2014)
Indonesia is a sovereign country. Sovereign does not only mean "denotation"; which is the state has the power of government that is not subject to other state power. Implementation of the state intended to realize the peoples welfare. If it is associated to the competition with other countries, then, we will know more about the role of the state in protecting its citizens in order to avoid "homo homini lupus" as what Hobbes said. So, this is the challenge of the welfare state, wherein it should not fail. The existence of state failure cases in providing protection for its citizens, especially in free trade has become a scourge for the people. Those people who are not able to compete in free trade, in the end, they will only be a spectator and do not have any role in AEC 2015. State efforts to protect people among others: increasing competitiveness and export volume, then, prioritizing the use of the goods / services in the country. In the regulation, it needs to set rules on the security measures of domestic products and supervision over circulation of goods and services, and by applying the Early Warning System to the possibility of a surge in imports.Â Keywords: Sovereign, Welfare State, Competitiveness, ASEAN Economic Community 2015